2016
DOI: 10.1016/j.biortech.2015.12.087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a magnetic field on the adsorptive removal of methylene blue onto wheat straw biochar

Abstract: Biochar pyrolyzed from wheat straw was innovatively used for the adsorptive removal of cationic dye methylene blue through exposure to a magnetic field. The adsorption capability of the biochar pyrolyzed at 200 °C exceeded that of samples pyrolyzed at higher temperatures. The surface acidic functional groups of wheat straw biochar were deduced to be more sensitive to the effects of the external magnetic field. The enhancement of the magnetic field achieved by increases in the initial dye concentration, and a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(51 citation statements)
references
References 33 publications
8
38
0
1
Order By: Relevance
“…The total content of O-containing groups (TCOG) including C-O, C=O, COO and CO 3 2− , an important parameter affecting the adsorption capability of biochars [40], generally decreased as pyrolysis temperature increased from 300 to 600 • C, as previously reported by Li [35]. Both C-O and C=O bonds sharply decreased, and COO and CO 3 2− basically remained unchanged, as the pyrolysis temperature increased from 300 to 400 • C. This might be due to the intense decomposition of cellulose and hemicellulose by breaking the C-O and C=O groups [41][42][43].…”
Section: Characterization Of Banana Pseudostem Biocharssupporting
confidence: 74%
See 1 more Smart Citation
“…The total content of O-containing groups (TCOG) including C-O, C=O, COO and CO 3 2− , an important parameter affecting the adsorption capability of biochars [40], generally decreased as pyrolysis temperature increased from 300 to 600 • C, as previously reported by Li [35]. Both C-O and C=O bonds sharply decreased, and COO and CO 3 2− basically remained unchanged, as the pyrolysis temperature increased from 300 to 400 • C. This might be due to the intense decomposition of cellulose and hemicellulose by breaking the C-O and C=O groups [41][42][43].…”
Section: Characterization Of Banana Pseudostem Biocharssupporting
confidence: 74%
“…The peaks at 1117 cm −1 and 1067 cm −1 represented alkoxy C-O and aromatic C-O stretching vibrations, respectively. The shift of C-O peaks also confirmed that aromatization took place as increasing pyrolysis temperature [35]. The peaks at 876 cm −1 and 781 cm −1 were assigned to Si-O-Si symmetric stretching vibrations [36].…”
Section: Characterization Of Banana Pseudostem Biocharsmentioning
confidence: 62%
“…The calculated equilibrium adsorption capacities were consistent with the obtained experimental results. Screening the literature, it was found that the equilibrium adsorption capacities of methylene blue and Hg on the current adsorbent were relatively close to that found on various adsorbents reported in the literature, considering low initial concentrations ranges 8, 9, 12, 15 .…”
Section: Resultssupporting
confidence: 79%
“…Conventional adsorbents like clay activated carbon and nanomaterials are usually used for the removal of heavy metal ions and dyes from wastewater 8 . Non-toxic, biodegradable and eco-friendly natural polymers such as cellulose, chitosan, and starch are also used because of their natural abundance, high efficiency and low cost 9 . For industrial applications, there is a need for more advanced properties of an adsorbent such as fast adsorption kinetics, high capacity, and temperature stability 1015 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, phenol and its derivatives have been evaluated in numerous studies, and 2,4-dichlorophenol was found to be fully adsorbed using a paper sludge/wheat husk biochar (Kalderis et al 2017). Biochar has also been assessed as an adsorbent for many types of organic dyes, such as methylene blue (Li et al 2016;Lonappan et al 2016), green malachite (Leng et al 2015), and methyl violet ). Thus, biochars derived from wheat straw were able to remove between 86.7% and 91.4% of methylene blue.…”
Section: Introductionmentioning
confidence: 99%